2022
DOI: 10.1101/2022.02.19.481089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted Down Regulation Of Core Mitochondrial Genes During SARS-CoV-2 Infection

Abstract: Defects in mitochondrial oxidative phosphorylation (OXPHOS) have been reported in COVID-19 patients, but the timing and organs affected vary among reports. Here, we reveal the dynamics of COVID-19 through transcription profiles in nasopharyngeal and autopsy samples from patients and infected rodent models. While mitochondrial bioenergetics is repressed in the viral nasopharyngeal portal of entry, it is up regulated in autopsy lung tissues from deceased patients. In most disease stages and organs, discrete OXPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 86 publications
5
25
0
Order By: Relevance
“…In line with the detected enrichment of accessible binding motifs for the inflammatory TF family, supervised hierarchical clustering further showed that SARS-CoV-2 infection induced the transcription of IFN-stimulated genes. In accordance with reported SARS-CoV-2-mediated impairment of mitochondrial biogenesis (Guarnieri et al, 2022), downregulated genes in SARS-CoV-2-infected samples were significantly associated (among others) with the downregulation of pathways driving mitochondrial oxidative phosphorylation (OXPHOS). The upregulation of chromatin silencing and nucleosome assembly pathways at the proteomic level in SARS-CoV-2-infected samples is consistent with SARS-CoV-2-ORF8-mediated chromatin compaction (Kee et al, 2021) and may represent the epigenomic mechanism underlying SARS-CoV-2-mediated host-shutoff (Finkel et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…In line with the detected enrichment of accessible binding motifs for the inflammatory TF family, supervised hierarchical clustering further showed that SARS-CoV-2 infection induced the transcription of IFN-stimulated genes. In accordance with reported SARS-CoV-2-mediated impairment of mitochondrial biogenesis (Guarnieri et al, 2022), downregulated genes in SARS-CoV-2-infected samples were significantly associated (among others) with the downregulation of pathways driving mitochondrial oxidative phosphorylation (OXPHOS). The upregulation of chromatin silencing and nucleosome assembly pathways at the proteomic level in SARS-CoV-2-infected samples is consistent with SARS-CoV-2-ORF8-mediated chromatin compaction (Kee et al, 2021) and may represent the epigenomic mechanism underlying SARS-CoV-2-mediated host-shutoff (Finkel et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…However, this change was seen only in Calu-3 cells, which are lung epithelial cells but not seen in Caco-2 and Huh-7 cells, indicating that different cell types may show different alterations in carbon metabolism upon the viral infection. Most recent targeted transcriptome analysis revealed impairment of mitochondrial OXPHOS and antioxidant gene expression in clinical samples of nasopharyngeal, heart, kidney and liver tissues, which was correlated with enhanced mtROS which stabilises HIF-1α [ 80 ], which is known to induce glycolysis [ 81 ] and repress mitochondrial oxygen consumption [ 82 ] as well. The study also confirms with the help of clinical autopsy samples that, with reducing viral load, mitochondrial integrity is rescued that repairs tissue damage.…”
Section: Mitochondrial Energetics Metabolism and Sars-cov-2 Infectionmentioning
confidence: 99%
“…Differentially expressed gene lists were created using the DESeq2 R package (58) by comparing injury and Sham conditions, with or without P110 treatment. Gene set enrichment analyses (GSEA) were performed using the desktop software (https://www.gsea-msigdb.org/gsea/index.jsp) (59, 60) using MitoCarta3.0 (61) and custom curated mitochondrial pathway (62) databases. Heatmaps were generated using the pheatmap R package.…”
Section: Methodsmentioning
confidence: 99%